Genus Apethistis Meyrick (Lepidoptera: Autostichidae: Autostichinae) new to China, with description of four new species - Wang, Yuqi; Wang, Shuxia (Zootaxa, 2017)
The genus Apethistis Meyrick, 1908 is recorded for the first time in China. Four new species are described: A. sinuata sp. nov., A. uncinata sp. nov., A. dentata sp. nov., and A. triangula sp. nov. Images of adult and genitalia of the new species are provided.